The properties of poly(Latic Acid) (PLA)/Hydroxyapatite (FsHAp) composite prepared through solvent casting techniques - Ismail Zainol (Tanjung Malim, 2023)
The properties of poly(Latic Acid) (PLA)/Hydroxyapatite (FsHAp) composite prepared through solvent casting techniques by Ismail Zainol